Estratégias de comercialização e perfil de cooperativas da agricultura familiar do Centro-Oeste e do Sul do Brasil - Harold, Carlos Alexandre da Silva (2023)
One of the aims of cooperatives is to organize production and marketing in order to find new markets and get away from dependence on intermediaries. They are therefore looking for strategies that will allow them to survive, develop and be autonomous in the running and advancement of their enterprises. With this in mind, the general aim of this study was to analyze the marketing and autonomy strategies of family farming cooperatives in the Central West and South regions of Brazil. Managers and members of six agricultural cooperatives were interviewed, one in Rio Grande do Sul, two in Paraná and three in Goiás, all of which are made up of family farmers and are involved in government institutional marketing programs. The results show that two cooperatives in Goiás and the one in Rio Grande do Sul are managed with the effective participation of their members. The cooperatives in Paraná and one in Goiás have a more corporate management model, with more decision-making by the organization's management. Access to credit presents difficulties in terms of guarantees and excessive bureaucracy, highlighting the organizations' weaknesses. Raising non-reimbursable funds was seen as the main source of investment. The organizations are dependent on institutional programs for fresh products. It can be concluded that there is a notorious lack of autonomy in family farming cooperatives, with significant dependence on public purchases via institutional programs, difficulties in operating in other markets and dependence on non-reimbursable resources for investments. Weaknesses in the quantity and quality of production were pointed out as the main challenge facing cooperatives, leading us to conclude that this is just the tip of a complex scenario of weaknesses in management and technical assistance and rural extension.